The Pathogenesis and Long-Term Consequences of COVID-19 Cardiac Injury - Siripanthong, Bhurint; Asatryan, Babken; Hanff, Thomas C.; Chatha, Salman R.; Khanji, Mohammed Y.; Ricci, Fabrizio; Muser, Daniele; Ferrari, Victor A.; Nazarian, Saman; Santangeli, Pasquale; Deo, Rajat; Cooper, Leslie T.; et al. (JACC. Basic to translational science, 2022)
•COVID-19 myocardial injury results from immune and hypercoagulability responses.•Long-term cardiac consequences of COVID-19 include structural and functional changes.•Myocarditis after COVID-19 vaccination is uncommon (highest risk in teenage males).•Larger population-based studies are necessary to validate these early results. The mechanisms of coronavirus disease-2019 (COVID-19)–related myocardial injury comprise both direct viral invasion and indirect (hypercoagulability and immune-mediated) cellular injuries. Some patients with COVID-19 cardiac involvement have poor clinical outcomes, with preliminary data suggesting long-term structural and functional changes. These include persistent myocardial fibrosis, edema, and intraventricular thrombi with embolic events, while functionally, the left ventricle is enlarged, with a reduced ejection fraction and new-onset arrhythmias reported in a number of patients. Myocarditis post-COVID-19 vaccination is rare but more common among young male patients. Larger studies, including prospective data from biobanks, will be useful in expanding these early findings and determining their validity. [Display omitted]